Energy Flow Analysis During the Tennis Serve: Comparison Between Injured and Noninjured Tennis Players. (November 2014) - Martin, Caroline; Bideau, Benoit; Bideau, Nicolas; Nicolas, Guillaume; Delamarche, Paul; Kulpa, Richard
Background: Energy flow has been hypothesized to be one of the most critical biomechanical concepts related to tennis performance and overuse injuries. However, the relationships among energy flow during the tennis serve, ball velocity, and overuse injuries have not been assessed. Purpose: To investigate the relationships among the quality and magnitude of energy flow, the ball velocity, and the peaks of upper limb joint kinetics and to compare the energy flow during the serve between injured and noninjured tennis players. Study Design: Case-control study; Level of evidence, 3. Methods: The serves of expert tennis players were recorded with an optoelectronic motion capture system. The forces and torques of the upper limb joints were calculated from the motion captures by use of inverse dynamics. The amount of mechanical energy generated, absorbed, and transferred was determined by use of a joint power analysis. Then the players were followed during 2 seasons to identify upper limb overuse injuries with a questionnaire. Finally, players were classified into 2 groups according to the questionnaire results: injured or noninjured. Results: Ball velocity increased and upper limb joint kinetics decreased with the quality of energy flow from the trunk to the hand + racket segment. Injured players showed a lower quality of energy flow through the upper limb kinetic chain, a lower ball velocity, and higher rates of energy absorbed by the shoulder and elbow compared with noninjured players. Conclusion: The findings of this study imply that improper energy flow during the tennis serve can decrease ball velocity, increase upper limb joint kinetics, and thus increase overuse injuries of the upper limb joints.